Effects of Refining Parameters on the Properties of Oil Palm Frond (OPF) Fiber for Medium Density Fibreboard (MDF) - Ibrahim Z.; Alias A.H.; Ramli R.; Wahab N.A.; Ahmad M.; Osman S.; Sheng E.L. (Penerbit Akademia Baru, 2023)
Studies on the manufacture of medium density fiberboard (MDF) from oil palm frond (OPF) fibre were conducted to provide a sustainable and feasible source of lignocellulosic materials. The quality and properties of the fibre are very important as it dictates the final MDF properties. The properties of fibre like fibre pH, buffering capacity, and morphology can influence most of the MDF performances. Refining condition is one of the most important factors which determine the properties of the refined fibre. In this study, the effects of different refining pressures and temperatures on OPF fibre were evaluated. The refining of OPF fibre was observed at four levels of refining parameters; which were categorized as low (2 bar at 130 C), medium (4 bar at 150 C), high (6 bar at 170 C), and severe (8 bar at 190 C). The refining heating time of 5 minutes was employed. The pH, buffering capacity, morphology, and the surface of the fibres were evaluated. The refined fibres were used to manufacture fibreboard panels at a target density of 720 kg/m3 and 12% urea formaldehyde (UF) resin. The panels physical (thickness swelling) and mechanical properties (bending and internal bonding strength) were then evaluated according to European Standard (EN 622-5, 2006). The results indicated that refining conditions affected the properties of the fibres and final boards. High steam pressure and temperature-induced pH changes in OPF fibres, leading to more acidic fibres and greater acid buffering capacity. The fibre separation was more adequate at this level and produced fibre with a smooth surface. Based on the test results for fibreboard properties, high steam pressure and temperature produced better dimensional stability of panels and bending and bonding strength. However, at the highest refining condition (severe level), the board performances began to deteriorate. The best performances of the samples were found for the panels made under refining conditions of 6 bar at 170 C. 2021. All Rights Reserved.